Предмет: Алгебра,
автор: Ананасинкавики
выполните ,пожалуйста
Приложения:
Ответы
Автор ответа:
0
x-4 = -(4-x)
тк знаменатель одинаковый, тогда:
(3x -1 -(2x+3)) /(4 -x) =(3x -1 -2x -3) /(4 -x) =(x -4)/(4 -x) = -(4 -x) /(4 -x) = -1
тк знаменатель одинаковый, тогда:
(3x -1 -(2x+3)) /(4 -x) =(3x -1 -2x -3) /(4 -x) =(x -4)/(4 -x) = -(4 -x) /(4 -x) = -1
Похожие вопросы
Предмет: Алгебра,
автор: topmaks995
Предмет: Другие предметы,
автор: Timka100600
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: Козачкова
Предмет: История,
автор: petrosyan96